A Game of Thrones - Martin, George R. R. (New York : Bantam Books, 1996)
The kingdom of the royal Stark family faces its ultimate challenge in the onset of a generation-long winter, the poisonous plots of the rival Lannisters, the emergence of the Neverborn demons, and the arrival of barbarian hordes.
aIncludes two maps covering the territory of A game of thrones on endpapers.
Keywords: Fiction